Atypical Presentation of Acquired Hypoganglionosis in a Patient Taking Clozapine - Catherine Gisi; Anamaria Munteanu; Lawrence Ku; Samuel French; Michael Fleischman; Viktor Eysselein (Case Reports in Gastrointestinal Medicine)
Acquired hypoganglionosis (HG) is a rare enteric gastrointestinal neuromuscular disorder previously associated with chronic inflammation that can lead to constipation, ileus, and even death. There is little known about the pathophysiology of acquired hypoganglionosis, and it is unclear if medications are related to the development of the disease. Clozapine is an atypical antipsychotic used to treat refractory schizophrenia that is well known for its side effects including agranulocytosis and gastrointestinal dysmotility. This is an unusual case of acquired hypoganglionosis in a patient with anticholinergic toxicity on clozapine therapy.